Nano-graphene oxide incorporated into PMMA resin to prevent microbial adhesion. Issue 4 (April 2018) - Lee, Jung-Hwan; Jo, Jeong-Ki; Kim, Dong-Ae; Patel, Kapil Dev; Kim, Hae-Won; Lee, Hae-Hyoung
Graphical abstract: Highlights: Polymethyl methacrylate (PMMA) incorporating nano-sized graphene oxide (nGO) led to improved mechanical properties. PMMA incorporating nGO exhibited an anti-adhesive effect against microbial species in artificial saliva. An increase in hydrophilicity was considered a possible mechanism of the antimicrobial-adhesive effects of nGO-PMMA. A sustained antimicrobial-adhesive effect was observed for up to 28 days. Abstract: Objective: Although polymethyl methacrylate (PMMA) is widely used as a dental material, a major challenge of using this substance is its poor antimicrobial (anti-adhesion) effects, which increase oral infections. Here, graphene-oxide nanosheets (nGO) were incorporated into PMMA to introduce sustained antimicrobial-adhesive effects by increasing the hydrophilicity of PMMA. Methods: After characterizing nGO and nGO-incorporated PMMA (up to 2 wt%) in terms of morphology and surface characteristics, 3-point flexural strength and hardness were evaluated. The anti-adhesive effects were determined for 4 different microbial species with experimental specimens and the underlying anti-adhesive mechanism was investigated by a non-thermal oxygen plasma treatment. Sustained antimicrobial-adhesive effects were characterized with incubation in artificial saliva for up to 28 days. Results: The typical nanosheet morphology was observed for nGO. Incorporating nGO into PMMA roughened its surface and increased its hydrophilicity without compromising flexural strength or surface hardness. An anti-adhesive effect after 1 h of exposure to microbial species in artificial saliva was observed in nGO-incorporated specimens, which accelerated with increasing levels of nGO without significant cytotoxicity to oral keratinocytes. Plasma treatment of native PMMA demonstrated that the antimicrobial-adhesive effects of nGO incorporation were at least partially due to increased hydrophilicity, not changes in the surface roughness. A sustained antimicrobial-adhesive property against Candida albicans was observed in 2% nGO for up to 28 days. Significance: The presence of sustained anti-adhesion properties in nGO-incorporated PMMA without loading any antimicrobial drugs suggests the potential usefulness of this compound as a promising antimicrobial dental material for dentures, orthodontic devices and provisional restorative materials.